Overview of material processing mechanisms in unconventional machining methods - Kovač, Pavel; Krajny, Zdenko; Soos, Ljubomir; Savković, Borislav (Journal of Production Engineering, 2021)
From the point of view of the concept itself, technology is a set of processes, rules and habits used in the production of various objects in the most diverse spheres of production, or human activity itself. Therefore, there are several designations and naming of production technologies in the professional literature. Historically, probably the oldest systematic designation and division of production technologies and processes is given as early as 1963 in the German standard: Begriffe der Fertigungsverfahren DIN 8580. The standard defines production processes for the production of geometrically certain solids. In the paper is shown explanations of mechanisms of machining when is used unconventional machining technologies.